STUDIES ON DIAGNOSTIC AND THERAPEUTIC APPROACH FOR URINARY TRACT INFECTION - S. R. KULKARNI,; R. R. PACHORI,; N. S. KULKARNI, (The Bioscan, 2011)
Globally urinary tract infection (UTI) is the second most common infectious presentation in the community. Due to an improper laboratory diagnosis along with the tremendous practice of evidence less therapy, UTI most often results in to life threatening complications. Hence, with the view to generate an easy approach of diagnosis.The present study on physical, chemical and microbiological examination of urine along with drug sensitivity have been carried out with known UTI female patients of reproductive age group. The present study enlighted, the predominant presence of albumin, with increased pus cells at least up to 30/ mf, epithelial cells up to 20/ mf, along with WBC up to 18 cu mm can be taken in to consideration as a diagnostic marker during the urine analysis. Also the positive test for the presence of E.coli with an existence of 72.72 % followed by Proteus species, S. aureus and Pseudomonas species with 54.54, 45.45 and 9% respectively can be used as a microbiological diagnostic marker for UTI. The present study also suggests that for therapy the Amoxicillin (30mcg) may be the choice of drug.